Effects of Massage Therapy :A literature review - zolriasatain, Fereshteh; bahriani, sayna (Advances in Nursing & Midwifery, 2011)
Background and Aim Development of technology in health care and its threats to providing holistic care has in a tendency of medical team specially nurses to use complementary and alternative medicine. Massage therapy is used widely by health care providers. In this article effects of massage therapy are discussed. Materials and Methods The PubMed, CINAHL, Science Direct, SID an Irandoc databases were searched using the keywords “massage” “ complementary therapy” and “alternative medicine” . The current review summarizes the findings of 40 articles, which were published between 1990 to 2009. Findings Effects of massage therapy include : relieving pain, specially Masculo-skeletal pains, positive effect on gastrointestinal signs such as indigestion and constipation, effect on physiological indexes including blood pressure, pulse, respiratory, temperature and oxygen saturation; infant's weight gain and decreasing sleep problems, improvement in range of motion and functions of respiratory and m asculo- skeletal systems beside immune system through reducing depression and increasing number of CD4 and ratio of CD4/CD8. Positive effects of massage have also been shown during pregnancy and labour. Conclusion Use of complementary therapies such as massage is part of professional goal of nursing. With understanding effects of massage as a one of the most common and safest complementary therapies we can provide holistic nursing care. Keywords: Massage, Complementary therapy,Adjunctive therapy